Datura leaf curl betastellite associated for the first time with Datura inoxia leaf curl syndrome in India. - Prajapat, Dr Rajneesh; Marwal, Avinash; Gaur, R K (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Begomovirus is one of the largest group of Bemisia tabaci transmitted plant viruses (family Geminiviridae) containing single-stranded circular DNA that encapsidated in geminate particles and prevalent in the tropical and subtropical regions of the world. In the present report we identified a begomovirus infecting Datura inoxia, a common toxic weed found in India annually. PCR product of complete betasatellite having an expected size 1.04 kb was obtained from infected plants samples. The PCR products were suitably cloned into pGEM-T vector and sequenced, having Accession number as JQ693149 (Datura leaf curl betasatellite). The betasatellite had showed highest nucleotide sequence identities of 93 % with Croton yellow vein mosaic betasatellite (HM143908). Rcombination analysis with RDP v.3.44 clearly indicates the portion of recombinant fragment of betasatellite infecting Datura inoxia is contributed from the two viruses prevailing at different geographical region, undoubtedly pointing towards the betasatellite evolution.